2016
DOI: 10.1523/jneurosci.2235-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Differentially Regulates Synaptic Plasticity in the Hippocampus and Spinal Cord by Microglia-Dependent Mechanisms after Peripheral Nerve Injury

Abstract: Clinical studies show that chronic pain is accompanied by memory deficits and reduction in hippocampal volume. Experimental studies show that spared nerve injury (SNI) of the sciatic nerve induces long-term potentiation (LTP) at C-fiber synapses in spinal dorsal horn, but impairs LTP in the hippocampus. The opposite changes may contribute to neuropathic pain and memory deficits, respectively. However, the cellular and molecular mechanisms underlying the functional synaptic changes are unclear. Here, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
205
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(221 citation statements)
references
References 51 publications
6
205
0
1
Order By: Relevance
“…However, this notion is based on in vitro analysis of cellular responses to LPS or cytokine administration (Corona, et al 2010; Guillemin, et al 2003) (Chiarugi, et al 2001; Schwarcz and Stone 2017). Consistent with a recent report (Liu, et al 2017), we also observed activation of microglia in the hippocampus in response to SNI. However, we observed that in response to SNI, KMO protein was mainly increased in NeuN-positive neuronal cells in the hippocampal dentate gyrus and not in the microglia.…”
Section: Discussionsupporting
confidence: 93%
“…However, this notion is based on in vitro analysis of cellular responses to LPS or cytokine administration (Corona, et al 2010; Guillemin, et al 2003) (Chiarugi, et al 2001; Schwarcz and Stone 2017). Consistent with a recent report (Liu, et al 2017), we also observed activation of microglia in the hippocampus in response to SNI. However, we observed that in response to SNI, KMO protein was mainly increased in NeuN-positive neuronal cells in the hippocampal dentate gyrus and not in the microglia.…”
Section: Discussionsupporting
confidence: 93%
“…We now show that expression of the equivalent cytokines is decreased in the SDH following PNL in mice with LRP1-deficient microglia. TNFα, IL-6, and IL-1β are known to modulate spinal cord synaptic transmission and play an important role in central sensitization (Kawasaki, Zhang, Cheng, & Ji, 2008;Liu et al, 2017;Obreja, Rathee, Lips, Distler, & Kress, 2002). Thus, the absence of demonstrable tactile allodynia in TAM-treated Cx3cr1-CreER T -LRP1 fl/fl mice may reflect either direct interaction of sLRP1 with SDH neurons or changes in the local concentration of other factors, such as TNFα, IL-6, and IL-1β, secondary to sLRP1-induced gene regulatory events.…”
Section: Discussionmentioning
confidence: 99%
“…Descending facilitation of neuropathic pain from the PAG is promoted by such glial cell activation in a CCI model [103]. The hippocampus has been reported to exhibit impaired longterm potentiation in SNI mice, an effect that was recently suggested to originate from the effects of tumor necrosis factor-alpha and microglial activation in this brain region [104]. This glia-driven change in synaptic plasticity and resultant mechanical hypersensitivity has also been reported in the primary somatosensory cortex in a mouse SNL model [105•].…”
Section: Changes In Brain Regionsmentioning
confidence: 99%